Coordinating Healthcare Under a Pluralistic Health Insurance System: The Case of Slovakia - Juraj NEMEC; David SPACEK; Michiel de VRIES (Transylvanian Review of Administrative Sciences, 2015)
The Slovak approach to decreasing health-care costs is based on a changed interpretation of the concept of ‘a minimum network of provid-ers’. This study describes the changes made in the healthcare system in Slovakia in order to keep it affordable. It shows how the initial inter-pretation of a minimum network as an assurance for general access to healthcare services slow-ly changed into a cutback making the minimum network an upper limit for healthcare. The study argues that the complexity of the network made for non-transparent policies, in which consulta-tion was nearly absent and vertical power be-came dominant, despite the semi-independence of actors in the network. This observation runs counter to the network theory suggestion that in complex networks, with semi-independent actors, vertical power becomes useless.